Oxygen vacancy induced electrical conduction and room temperature ferromagnetism in system BaSn1−xNixO3 (0 ⩽ x ⩽ 0.20). (2nd November 2017) - Kumar, Upendra; Ansaree, Md Jawed; Verma, Atul Kumar; Upadhyay, Shail; Gupta, Govind
Abstract: Powder and ceramics of few compositions of BaSn1− x Ni x O3 (with x   =  0, 0.05, 0.10 and 0.20) have been prepared bysolid-state reaction route. Synthesized samples have been characterized using XRD, FTIR, SEM and XPS techniques. XPS studies have shown that all samples contain a significant number of oxygen vacancies (VO ), Ba is present in the Ba 2+ state, Sn is present in both Sn 2+ and Sn 4+ states and Ni exists mainly in the Ni 2+ state. The AC conductivity spectra of all compositions followed universal Johnscher's power law and the time-temperature superposition principle (TTSP). Above 300 °C conduction in these samples is governed by long-range diffusion of doubly ionized oxygen vacancies ( V O · · ). M - H loop at room temperature shows that undoped BaSnO3 is ferromagnetic with saturation magnetization ( M s ) ~ 5.46  ×  10 −3 emu g −1 and coercive field ( H c ) ~ 540 Oe, due to spins of electrons trapped in oxygen vacancies (F-center) and direct interaction between F-centers. Ni-doped samples exhibit both ferromagnetic and paramagnetic behavior and paramagnetic contribution increases with doping concentration. The room temperature magnetic parameters have been extracted by fitting the experimental data to the bound magnetic polaron (BMP) model. The saturation magnetization increases whereas coercive field decrease with increasing concentration of dopant (Ni).